Fantastically Great Women Who Changed The World - Pankhurst, Kate (London Bloomsbury Publishing Plc, 2016)
Kate Pankhurst, descendent of Emmeline Pankhurst, has created this wildly wonderful and accessible book about women who really changed the world. Discover fascinating facts about some of the most amazing women who changed the world we live in. Fly through the sky with the incredible explorer Amelia Earhart, and read all about the Wonderful Adventures of Mary Seacole with the number one best-selling children's non-fiction title in the UK market this year. Bursting full of beautiful illustrations and astounding facts, Fantastically Great Women Who Changed the World is the perfect introduction to just a few of the most incredible women who helped shaped the world we live in. List of women featured: Jane Austen, Gertrude Ederle, Coco Chanel, Frida Kahlo, Marie Curie, Mary Anning, Mary Seacole, Amelia Earhart, Agent Fifi, Sacagawa, Emmeline Pankhurst, Rosa Parks, Anne Frank